2007
DOI: 10.1007/s11060-007-9439-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of stem cell markers in human astrocytomas of different WHO grades

Abstract: According to new hypotheses astrocytomas/gliomas either arise from or attract neural stem cells. Biological markers, particularly antigenic markers, have played a significant role for the characterization of these tumour stem cells (TSCc). Because these studies have been performed with single experimental samples mostly from gliomas, we investigated the expression of the stem cell markers CD133/Prominin, Nestin, Sox-2, Musashi-1, CXCR4, Flt-4/VEGFR-3 and CD105/Endoglin in 72 astrocytomas of different WHO-grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
135
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(155 citation statements)
references
References 66 publications
17
135
0
3
Order By: Relevance
“…Many markers potentially specific for GSCs have been proposed such as A2B5 cell surface ganglioside epitope (A2B5) [26,27], aldehyde dehydrogenase (ALDH) [28], BMI1 polycomb ring finger oncogene (BMI1) [29,30], fucosyltransferase 4 (FUT4) (CD15) [31], Thy-1 cell surface antigen (Thy-1) (CD90) [32], prominin-1 (PROM1) (CD133) [5,6], chemokine (C-X-C motif) receptor 4 (CXCR4) [33], inhibitor of DNA binding 1 (ID1) [34], integrin α6 (ITGA6) [35], L1 cell adhesion molecule (L1CAM) [36], maternal embryonic leucine zipper kinase (MELK) [37], musashi-1 (msi1) [38], nestin (NES) [38][39][40], octamer-binding transcription factor 4 (OCT4) [41], OLIG2 [42] and SOX2 [38,[43][44][45]. Among these, much attention has been given to CD133, which is currently used to identify and isolate GSCs [40,43,[46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many markers potentially specific for GSCs have been proposed such as A2B5 cell surface ganglioside epitope (A2B5) [26,27], aldehyde dehydrogenase (ALDH) [28], BMI1 polycomb ring finger oncogene (BMI1) [29,30], fucosyltransferase 4 (FUT4) (CD15) [31], Thy-1 cell surface antigen (Thy-1) (CD90) [32], prominin-1 (PROM1) (CD133) [5,6], chemokine (C-X-C motif) receptor 4 (CXCR4) [33], inhibitor of DNA binding 1 (ID1) [34], integrin α6 (ITGA6) [35], L1 cell adhesion molecule (L1CAM) [36], maternal embryonic leucine zipper kinase (MELK) [37], musashi-1 (msi1) [38], nestin (NES) [38][39][40], octamer-binding transcription factor 4 (OCT4) [41], OLIG2 [42] and SOX2 [38,[43][44][45]. Among these, much attention has been given to CD133, which is currently used to identify and isolate GSCs [40,43,[46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, much attention has been given to CD133, which is currently used to identify and isolate GSCs [40,43,[46][47][48][49][50]. Despite the fact that this is the most widely used antigen for enrichment of GSCs, there are several arguments to suggest the existence of CD133-negative GSCs: CD133 is not detectable in many fresh GBM specimens [14,31,51], and some studies revealed CD133-negative GBM cultures with the ability to self-renew and to form tumours in xenotransplantation assays [14,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Nestin has been detected in brain tumors such as pilocytic astrocytomas and malignant gliomas including glioblastoma multiforme (27,28,52,53). Our results showed that STM91-01, TTC549 and TTC1240 expressed nestin, which was detected by RT-PCR and Western blotting.…”
Section: Discussionmentioning
confidence: 54%
“…Msi-1 is an RNA binding protein which is preferentially expressed in stem-cells, functions as a translational repressor (56)(57)(58), and is widely used as a molecular marker to identify stem cells in embryos and adult tissues (26)(27)(28)(29). In our study, Msi-1 was expressed in five MRT cell lines except TTC642, which originated from a neck mass.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation